Quality Evaluation of Self-Adaptive Systems: Challenges and Opportunities - de Sousa, Amanda Oliveira; Bezerra, Carla I. M.; Andrade, Rossana M. C.; M. Filho, José M. S. (Companion Proceedings of the Brazilian Symposium on Software Engineering (SBES); 2019: Companion Proceedings of the 33th Brazilian Symposium on Software Engineering, 2020)
Self-adaptive systems (SAS) can adapt their behavior to suit user preferences or contexts, as well as monitor their performance and adjust it if necessary. In addition to adaptation operations, self-adaptive systems communicate with sensors, actuators, and other devices. Due to the complexity and dynamism of SAS, many situations can compromise the functioning of the system, such as faults in adaptations, low performance to execute tasks, and context inconsistencies. To prevent the system of these problems, it is essential to ensure high levels of quality. However, due to the peculiarities of these systems, there are still challenges to perform quality evaluations in these systems. In this sense, this paper proposes a discussion about the quality evaluation of self-adaptive systems in the last years. As a result, we identify challenges, limitations and research opportunities related to SAS quality evaluation.